2013
DOI: 10.1002/jcp.24256
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α enhances the transcription of smad ubiquitination regulatory factor 1 in an activating protein‐1‐ and runx2‐dependent manner

Abstract: Smad ubiquitination regulatory factor 1 (Smurf1) is an E3 ubiquitin ligase that negatively regulates osteoblast differentiation. Although tumor necrosis factor-α (TNF-α) has been shown to increase Smurf1 expression, the details of the regulatory mechanisms remain unclear. Here, we investigated the molecular mechanism by which TNF-α stimulates Smurf1 expression in C2C12 and primary cultured mouse calvarial cells. TNF-α treatment rapidly induced the activation of NF-κB and MAPKs. Smurf1 induction by TNF-α was bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The same trend, down-regulation of these adhesion molecules, was found in our previous study where neutrophils were stimulated by CXC-motif chemokine 8 (CXCL8); 20 however, as multiple literature precedents also reported up-regulation of those molecules from neutrophils after stimulation, 4143 this unexpected down-regulation was unexplained in the previous study. Upon close examination of precedent work done in co-culture, 4143 we see that CD11b and CD66b expressions were up-regulated in EC-treated cells.…”
Section: Discussionsupporting
confidence: 82%
“…The same trend, down-regulation of these adhesion molecules, was found in our previous study where neutrophils were stimulated by CXC-motif chemokine 8 (CXCL8); 20 however, as multiple literature precedents also reported up-regulation of those molecules from neutrophils after stimulation, 4143 this unexpected down-regulation was unexplained in the previous study. Upon close examination of precedent work done in co-culture, 4143 we see that CD11b and CD66b expressions were up-regulated in EC-treated cells.…”
Section: Discussionsupporting
confidence: 82%
“…Tumor necrosis factor‐alpha has been documented to regulate bone remodeling by suppressing osteogenesis and activating osteoclastogenesis . Quite a few signaling pathways are involved in mediating the effects of TNFα on osteogenesis as reported . Among them, SMURF1 seems particularly notable because SMURF1 itself is a well‐known negative regulator of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF transgenic mice, which exhibited significantly decreased bone volume, had significantly lower SMAD1 protein level than wild‐type mice . In vitro studies demonstrated that TNFα suppressed both osteoblast function and MSCs osteogenesis via upregulating SMURF1, which may target SMAD1/5 or RUNX2 . Additionally, BMP2‐induced osteogenic differentiation and bone formation were dramatically inhibited in inflammatory environment .…”
Section: Introductionmentioning
confidence: 99%
“…This may occur through activation of MAPK signaling, which is induced by tumor necrosis factor (TNF)-α and TNF-related weak inducer of apoptosis (TWEAK) (22). In addition, Ras/ERK1/2 MAPK signaling, as the probable pathway in inflammatory bone resorption, is activated by TNF-α via the enhanced transcription of Smad ubiquitination regulatory factor 1 and is dependent on Runx2, which activates bone formation-related cytokines (23,24). ERK1/2-Runx2 signaling is also related to mechanical stress (25), which may explain why periodontitis frequently occurs during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%